Mariella Bettineschi : N.Y.C. Groundzero. - Pietrantonio, Giacinto Di; Biagiotti Arte Contemporanea, Firenze; MONA (Museum of New Art), Detroit (Firenze : Biagiotti Arte Contemporanea, 2002)
The work by Mariella Bettineschi is an installation of 56 photographs of objects and messages left by people who have visited New York Ground Zero. This New York site is becoming a sanctuary, a testimony that people, after the September 11 tragedy, are capable of reacting with an united strenght that goes beyond different cultures, skin colours, ages, nationalities and religions.
gr. tent., special projects [4 p.]
ind. tent. [2 p.]
Engels
Italiaans
Mariella Bettineschi : N.Y.C. Groundzero. Biagiotti Arte Contemporanea Firenze / MONA (Museum of New Art) Detroit. 2002-05-16. 2002-07-13. 2002-06-18. 2002-08-24
kunstcatalogus
Keywords: Bettineschi, Mariella; New York